"Un Sacco di Sport": Design Toward a New Socially Responsible Production Chain for Dismissed Textiles. (1st September 2020) - Campagnaro, Cristian; Ceraolo, Sara
Abstract: The following article is a position paper based on a case study of "Un sacco di sport, " a design driven research project for the development of a new socially responsible production chain for dismissed textiles resulting from promotional campaigns of city events. The project is based on the hypothesis that, in the city of Turin, a strategy based on the upcycling of dismissed textiles offers unseen opportunities for the development of innovative models of education for design students and circular economy chains, based on both reciprocity and social inclusion. This will be addressed in the paper through a description of the different phases of the project, with a focus on the potential offered by the dismissed textiles to shape design concepts developed by students of the Meta-design course at Politecnico di Torino. In addition, this article will underline the importance of collaboration in strengthening the relationship between the numerous stakeholders that took part in the process. The methodology adopted by the research presents a participative orientation and a collaborative design approach. This approach, tested by "Un sacco di sport, " was significantly influenced by the combination of relational resources, skills, and capabilities offered by the stakeholders. Due to the ongoing nature of the project, it has produced a number of significant outcomes that contribute to discourse around the value of waste materials, the importance of collaboration in strategic processes, and the role of design for the promotion of new frameworks of active citizenship. At the same time, issues for further research have been identified, especially in regard to the ambition to make projects such as "Un sacco di sport" the basis for a new policy-model for the city of Turin in relation to the valorization of the dismissed textiles, based on collaboration and social inclusion. This paper positions the research toward this ambition.